The Impact of Doctor-Patient Communication on Patient Satisfaction: A Systematic Review. - Kaur, Upvanjeet; Jyoti, Jyoti; Jyoti, Jyoti (Journal of Neonatal Surgery, 2025)
Background: A key factor in determining patient satisfaction and the foundation of high-quality healthcare is effective doctor-patient communication. In addition to sharing clinical knowledge, it also entails empathy, active listening, and collaborative decision-making. Improving healthcare experiences requires an understanding of the wider influence of communication on patient satisfaction in various healthcare settings.By defining important communication components that affect patient perceptions and investigating demographic and contextual changes, this systematic review investigates the relationship between doctor-patient communication and patient satisfaction. Methods: PRISMA standards were followed in conducting a systematic review. Relevant studies published in English were found by searches in PubMed, Scopus, Web of Science, and PsycINFO. Studies examining the effect of doctor-patient communication on patient satisfaction in primary care, hospital, or outpatient settings were included in the inclusion criteria. A total of 1,164 participants from 12 trials satisfied the inclusion requirements. Data extraction was centered on statistical results, patient satisfaction metrics, and communication elements. Validated instruments like the Cochrane Risk of Bias Tool and the Newcastle-Ottawa Scale were used to evaluate the quality of the study. Results: Patient satisfaction and doctor-patient communication were found to be strongly positively correlated (p<0.05 in 10 out of 12 studies). Significant predictors of satisfaction included empathy (p<0.01), active listening (SMD=0.62), and explicit explanations (SMD=0.55). Communication quality and satisfaction were more strongly correlated with older persons and female patients, while satisfaction levels varied more in hospital settings. Conclusions: Enhancing patient satisfaction and the general quality of healthcare can be achieved by using patient-centered techniques and focused training to improve doctor-patient communication. Long-term effects and cultural influences should be investigated in future studies.